Effects of decavanadate and insulin enhancing vanadium compounds on glucose uptake in isolated rat adipocytes - Pereira, Maria João (2012)
The effects of different vanadium compounds namely pyridine-2,6-dicarboxylatedioxovanadium(V) (V5-dipic), bis(maltolato) oxovanadium(IV) (BMOV) and amavadine, and oligovanadates namely metavanadate and decavanadate were analysed on basal and insulin stimulated glucose uptake in rat adipocytes. Decavanadate (50 lM), manifest a higher increases (6-fold) on glucose uptake compared with basal, followed by BMOV (1 mM) and metavanadate (1 mM) solutions (3-fold) whereas V5 dipic and amavadine had no effect. Decavanadate (100 lM) also shows the highest insulin like activity when compared with the others compounds studied. In the presence of insulin (10 nM), only decavanadate increases (50%) the glucose uptake when compared with insulin stimulated glucose uptake whereas BMOV and metavanadate, had no effect and V5 dipic and amavadine prevent the stimulation to about half of the basal value. Decavanadate is also able to reduce or eradicate the suppressor effect caused by dexamethasone on glucose uptake at the level of the adipocytes. Altogether, vanadium compounds and oligovanadates with several structures and coordination spheres reveal different effects on glucose uptake in rat primary adipocytes.